An Inhibitor of the Interaction of Survivin with Smac in Mitochondria Promotes Apoptosis. Issue 22 (24th July 2019) - Park, Seong‐Hyun; Shin, Insu; Park, Sang‐Hyun; Kim, Nam Doo; Shin, Injae
Abstract: Herein we report the first small molecule that disrupts the survivin‐Smac interaction taking place in mitochondria. The inhibitor, PZ‐6‐QN, was identified by initially screening a phenothiazine library using a fluorescence anisotropy assay and then conducting a structure–activity relationship study. Mutagenesis and molecular docking studies suggest that PZ‐6‐QN binds to survivin similarly to the known Smac peptide, AVPI. The results of the effort also show that PZ‐6‐QN exhibits good anticancer activity against various cancer cells. Moreover, cell‐based mechanistic studies provide evidence for the proposal that PZ‐6‐QN enters mitochondria to inhibit the survivin‐Smac interaction and promotes release of Smac and cytochrome c from mitochondria into the cytosol, a process that induces apoptosis in cancer cells. Overall, the present study suggests that PZ‐6‐QN can serve as a novel chemical probe for study of processes associated with the mitochondrial survivin‐Smac interaction and it will aid the discovery of novel anticancer agents. Abstract : A Smac in the face : We have developed the first small molecule, PZ‐6‐QN, that disrupts the survivin‐Smac interaction taking place in mitochondria. This substance binds to survivin similarly to the known Smac peptide, AVPI, and exhibits good anticancer activity against various cancer cells. PZ‐6‐QN enters mitochondria to inhibit the survivin‐Smac interaction and promotes release of Smac and cytochrome c from mitochondria into the cytosol, a process that induces apoptosis in cancer cells.